Kompetensi Emosi (Ekspresi dan Pemahaman Emosi) pada Anak Usia Prasekolah - Tiara Erlita; Zainal Abidin (Faculty of Ushuluddin and Humanities, 2020)
Children’s emotional competence will affect their psychosocial health. The purpose of this study is to provide an overview of emotional competency (expression and understanding) in preschool children (aged 4-5 years) in kindergarten “X” Jatinangor. This research uses qualitative method with a case study approach. The research subjects were children aged 4-5 years who attended kindergarten ‘X” Jatinangor. The research instrument used interviews and observations of the subject as the main participants and interviews with parents amd teachers as secondary participants. Data analysis used thematic analysis. This Study found that emotional competence which includes the subject’s ability to express and understand emotions as follows: all subjects could express emotion nonverbally, but not all subjects were able to express emotions they felt verbally and all subjects could understand the emotions that are felt but were still limited in labeling emotions appropriately. Associated with children’s limitations in emotional labelling, parents and teachers need to provide an understanding of emotional labels felt by children.